Niemiecko-polski konflikt o Górny Śląsk w latach 1918–1922 w perspektywie wybranych powieści autobiograficznych Ernsta von Salomona - Walkowiak, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The German–Polish conflict about Upper Silesia from 1918–1922, which is one of the most important historical and political issues in the literary work of Ernst von Salomon, particularly in his autobiographical novels, is briefly analysed in the context of his turbulent biography, his work and autobiographical strategies. In von Salomon’s novels, the sheer conflict seen as a fight over new frontiers in Central and Eastern Europe in 1918–1922 becomes a subjective narration which results, to a large extent, from his involvement in the postulates of the German national revolution as one of the trends of the Conservative Revolution in Germany between 1918 and 1933. At the end of the paper, this conflict in Salomon’s literary perspective is briefly analysed around key issues based on selected examples from his autobiographical novels.